Why the hell are cuss words not included in teaching of Portuguese as foreign language?! - Sharma, Manjulata (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
This brief study of Brazilian swear words is an attempt to understand the non-inclusion of swear words in the teaching of Portuguese as a foreign language as they are considered as taboo lexicon from the point of view of the institutionalized normative standard language supervised periodically by the Academies. I argue that, since the swear words form a part of the repertoire of popular colloquial vocabulary, they represent the popular culture through their intensity of emotional expression and contextual use. I use the Theory of Lexiculture, proposed by Galisson (1987), and Functional Grammar, by Halliday (2004), to argue that swear words should be introduced through figures of speech such as euphemism and dysphemism, as well as comparisons between swear words of native language of the learner and that of the target language to give the learner a better understanding of the emotional aspect of the language and to foster better pragma-linguistic, socio-pragmatic competence and intercultural competence for the learner of Portuguese as a Foreign Language. ———————————————————————————— POR QUE DIABOS PALAVRÕES NÃO SÃO INCLUÍDOS NO ENSINO DE PORTUGUÊS COMO LÍNGUA ESTRANGEIRA?! Este trabalho tem intuito de investigar a exclusão dos palavrões brasileiros no ensino do português como língua estrangeira por serem considerados vocabulário tabus do ponto de vista da língua normativa institucionalmente padronizada e periodicamente supervisionada pelas Academias. Eu pressuponho que desde os palavrões formam o repertório do léxico coloquial popular, eles representam a cultura popular através da intensidade da expressão afetiva e o uso contextual. Eu pretendo utilizar a Teoria de Lexicultura de Galisson (1987) e Gramática Funcional de Halliday (2004) para afirmar que os palavrões devem ser apresentados através de ato da fala como eufemismo e disfemismo bem como através de estudos comparatistas entre a língua-alvo e a língua materna, para apresentar ao discente uma compreensão melhor do aspecto emotivo da língua com o intuito de fundar nele a noção de competências pragma-linguística, sócio pragmática e interculturais do PLE. — Original em inglês.